Understanding the Complexities of Child Marriage and Promoting Education to Prevent Child Marriage in Indramayu, West Java - Nurmila, Nina; Windiana, Wiwin (Universitas Islam Negeri Mataram, 2023)
The problem of child marriage in Indonesia is complex. There are many factors affecting the incidence of child marriage, such as poverty, lack of education, religious belief, social pressure, and limited employment opportunities. This paper aims to understand the complexities of child marriage in Indramayu, West Java. The Indonesian government has tried to eliminate child marriage, such as by amending the Law on the minimum age of marriage from 16 to 19 years old for girls. This paper argues that due to the complex problems of child marriage, eliminating child marriage requires many efforts to address the causes of child marriage, not only by amending the Law. This research is feminist research, which combines knowledge production with activism. It does not merely produce